Effects of CYP2D6 Genotypes on Venlafaxine Metabolism in Japanese Psychiatric Patients With Depression. Issue 5 (October 2021) - Komahashi-Sasaki, Hazuki; Yasui-Furukori, Norio; Sasaki, Taro; Shinozaki, Masataka; Hayashi, Yuki; Kato, Kazuko; Inoue, Yoshimasa; Tsuchimine, Shoko; Watanabe, Takashi; Sugawara, Norio; Shimoda, Kazutaka
Abstract : Background: Venlafaxine (VEN) is primarily metabolized by CYP2D6. Although several studies have reported the significant effects of CYP2D6 on VEN and O-desmethylvenlafaxine (ODV) pharmacokinetics in Whites, limited data are available regarding the effects of the Asian-specific CYP2D6 genotype on VEN metabolism. This study evaluated the effects of the CYP2D6*10 and CYP2D6*5 genotypes on the steady-state plasma concentrations of VEN and ODV in Japanese patients. Methods: This study included 75 Japanese patients with depression who were treated with VEN. Steady-state plasma concentrations of VEN and ODV were measured using liquid chromatography. Polymerase chain reaction was used to determine CYP2D6 genotypes. A stepwise multiple regression analysis was performed to analyze the relationship between independent variables (sex, age, smoking habit, and number of mutated alleles, CYP2D6*10 and CYP2D6*5), subject-dependent variables (plasma concentrations of VEN and ODV [all corrected for dose and body weight]), and the ODV/VEN ratio. Results: Significant correlations were observed between the daily dose of VEN (corrected for body weight) and plasma concentrations of VEN (r = 0.498, P < 0.001) and ODV (r = 0.380, P = 0.001); ODV plasma concentrations were approximately 3.2 times higher than VEN plasma concentrations (VEN versus ODV = 18.60 ng/mL versus 59.10 ng/mL). VEN plasma concentrations (corrected for dose and body weight) did not differ with differing numbers of CYP2D6-mutated alleles. However, the ODV/VEN ratio decreased as the number of mutated CYP2D6 alleles increased ( P = 0.001). Conclusions: This is the first study to examine the effects of CYP2D6*10 in a clinical setting. Although no effects on the plasma concentrations of VEN or ODV were observed, CYP2D6 polymorphism affects the ODV/VEN ratio. Further studies are needed to confirm the clinical relevance of these findings.